2020
DOI: 10.3390/oceans1010002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Methods for Measuring Sea Surface Temperature When Surfing

Abstract: Nearshore coastal waters are among the most dynamic regions on the planet and difficult to sample from conventional oceanographic platforms. It has been suggested that environmental sampling of the nearshore could be improved by mobilising vast numbers of citizens who partake in marine recreational sports, like surfing. In this paper, we compared two approaches for measuring sea surface temperature (SST), an Essential Climate Variable, when surfing. One technique involved attaching a commercially-available min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…Note for the iButton, Brewin et al [40] previously reported a median (not mean as used here) difference of 0.283 K for these experiments. These differences were within the accuracies stated by the sensor manufacturers, with the TidbiT v2 sensors accurate to 0.2 K over a range of 273.15 to 323.15 K, and the iButton 0.5 K over a range of 263.15 to 333.15 K. The differences between the TidbiT v2 sensor and the Themometrics ES 225 temperature probe (δ = 0.089) were also consistent with similar laboratory tests of the TidbiT v2 sensors in other studies [27,35], for example, Brewin et al [27] reported differences (δ) of 0.04 to 0.15 K for five TidbiT v2 sensors. The differences between the probe and the TidbiT v2 and iButton sensors (δ = 0.089 and δ = 0.292, Figure 2) were relatively systematic over the temperature range tested (Figure 2), and consequently, were removed from all data collected using these sensors in subsequent analysis.…”
Section: Statistical Testssupporting
confidence: 86%
See 2 more Smart Citations
“…Note for the iButton, Brewin et al [40] previously reported a median (not mean as used here) difference of 0.283 K for these experiments. These differences were within the accuracies stated by the sensor manufacturers, with the TidbiT v2 sensors accurate to 0.2 K over a range of 273.15 to 323.15 K, and the iButton 0.5 K over a range of 263.15 to 333.15 K. The differences between the TidbiT v2 sensor and the Themometrics ES 225 temperature probe (δ = 0.089) were also consistent with similar laboratory tests of the TidbiT v2 sensors in other studies [27,35], for example, Brewin et al [27] reported differences (δ) of 0.04 to 0.15 K for five TidbiT v2 sensors. The differences between the probe and the TidbiT v2 and iButton sensors (δ = 0.089 and δ = 0.292, Figure 2) were relatively systematic over the temperature range tested (Figure 2), and consequently, were removed from all data collected using these sensors in subsequent analysis.…”
Section: Statistical Testssupporting
confidence: 86%
“…The Smartfin records temperature continuously at 1/6 Hz using two different sensors, one within the body (motherboard) of the Smartfin (internal), the other placed on the tip of the fin (external). The external temperature sensor is a MAX31725 temperature circuit (see [34] for technical details) and was used in the study, as it has a quicker response and a higher precision and resolution than the internal sensor (e.g., see [35]). When submerged, the sensible part of the external temperature sensor is located at 0.1 m depth.…”
Section: The Simple Oceanographic Floating Device (Sod)mentioning
confidence: 99%
See 1 more Smart Citation
“…For these near-surface sensors, following the recommendations of Castillo and Lima [23], the installation will be with their long surface vertical to the sea surface in order to be less affected/biased due to direct solar radiation heating. This will also provide the most accurate method for investigating any stratification phenomena in the study area, since it will as much as possible prevent direct solar radiation heating-which, when using unshaded loggers, can result in areas with transparent clear waters, with erroneously high underwater temperature measurements, according to Bahr et al [48] and Brewin et al [49]. A land-based meteorological station is also going to be installed in the vicinity of the study area, so that it will be possible to investigate and quantify any correlations between atmospheric conditions and satellite SST measurement anomalies, following the methods of Brewin et al [21].…”
Section: Discussionmentioning
confidence: 99%
“…The Sonic Kayak system sets itself apart from these projects as the environmental data is geolocated and can be collected while moving, allowing very quick mapping without the need for multiple sets of equipment. A similar initiative, the Smartfin (https://smartfin.org/) is close in its aims, but is specific to surfboards and stand-up-paddleboards (as the electronics are embedded within a fin), currently only measures temperature, and is not open source so is not available for people to build or develop themselves (Brewin et al 2020).…”
Section: Introductionmentioning
confidence: 99%